OPTIMIZING A FINANCIAL STRATEGY FOR A STRONG BUSINESS SUSTAINABILITY - Rabiyatul Jasiyah; Suriadi; I Wayan Sujana (CV. Adiba Aisha Amira, 2025)
There are many important factors that influence the success of a business, one of which is financial strategy. Basically, finance is the basis for company operations which must be managed well through financial management. For the smooth running and sustainability of a business in the long term, a well-thought-out financial strategy is needed. Financial strategy is one of the pillars of a business. Sustainability in a business context refers to a form of accountability in strategic decision making. The strategy formed in business is how the business can develop, be accountable, and generate profits. The method used in this article is the study method. Literature studies can be obtained from various sources, including journals, books, documentation, the internet and libraries. This research discusses corporate finance theory, sustainability theory, business strategy theory, and the integration between finance and sustainability.